Biocatalytic conversion of methane – selected aspects. (December 2019) - Kasprzycka, Agnieszka; Lalak-Kańczugowska, Justyna; Walkiewicz, Anna; Bulak, Piotr; Proc, Kinga; Stępień, Łukasz
Graphical abstract: Highlights: There is reported recently concerning molecular studies and biotechnological approaches to utilize natural properties of methanotrophs. Enzymatic mechanisms and genetic tools developed to improve the efficiency of methanotrophs seem to be the most important research direction. Microbiological electrochemical technologies can be regarded as one of the most promising direction for development of future technologies. Abstract : In this review we summarize the findings reported recently concerning molecular studies and biotechnological approaches to utilize natural properties of methanotrophs in the efforts to minimize human influence on the environment. Most important enzymatic mechanisms were described, along with the groups of microorganisms responsible for these. Moreover, genetic tools designed to improve the efficiency of methanotrophs have been presented including modern gene-editing, systems and synthetic biology, as well as the metabolic modelling methods. Additionally, practical problems in the application of effective processes in large scale were shown, including slow growth and low cell density of cultured methanotrophs. Finally, the microbiological electrochemical technologies, such as direct energy generation (microbiological fuel cells or MFC), bioelectrochemical systems (BES), microbiological electrochemical systems (MES) are discussed.